Participants’ Perceptions of an HIV/AIDS Workshop - Young, Wendy I. (Canadian Journal of Counselling and Psychotherapy, 2011)
This brief report describes the perceptions of individuals who attended an educational program that targets HIV-positive people. Analysis of quotes from participants in a 90-minute focus group revealed three benefits of attending the workshop (empowerment, patient-physician relationship, and knowledge of medications). Four ways to improve the workshop were identified: peer support and support groups, additional information on medications, nutrition, and more information about the disease. The findings suggest that there may be an unmet need for counselling. Counselling practitioners could make further contributions to the systematic development, implementation, and evaluation of theory-based programs for people with a chronic disease.